Aux origines de l'identité franco-ontarienne : Éducation, culture, économie - Gaffield, Chad (University of Ottawa Press, 1993)
During the 1880s, Francophones in Eastern Ontario formulated a definition of their community that was both rooted in the past and derived from contemporary circumstances. Indeed, it was as a result of the controversy over the language of instruction in Ontario that the Franco-Ontarian identity emerged. From 1830, eastern Ontario, especially Prescott County, was the geographic junction of English and French Canada, the buckle of the bilingual belt. Thus, immigration from Quebec transforms this region, from a border zone where a sparse English-speaking population lives, into a sector with a French-speaking majority. From then on, all the attention of the province turned to this county; the controversy over the language of instruction intensified particularly after 1885, when the Ontario government adopted a series of measures intended to restrict the use of French in the province's schools. Chad Gaffield here examines the language question in relation to the social history and cultural identity of Eastern Ontario. It directly compares the writings of authorities and various social leaders in 19th century Ontario with the actual opinions and experience of residents of that region.